A novel enzyme-mediated gold nanoparticle synthesis and its application for in situ detection of horseradish peroxidase inhibitor phenylhydrazine. (15th November 2017) - Parashar, Abhinav; Sachin Kedare, Prachi; Alex, Sruthi Ann; Chandrasekaran, N.; Mukherjee, Amitava
Abstract : Biocatalyzed gold nanoparticle synthesis for the in situ detection of horseradish peroxidase inhibitor (phenylhydrazine) has been demonstrated. Abstract : The biocatalytic growth of metal nanoparticles for the detection of environmentally relevant chemical molecules is a recently exploited strategy. The present work provides a new synthesis methodology for gold nanoparticles (GNPs), which could be enzymatically modulated by horseradish peroxidase (HRP). Gold seeds (∼10 nm) were prepared initially by the reduction of HAuCl4 using a minimal concentration of NaBH4, and the further biocatalyzed GNP formation was assisted by HRP, its substrate, and hydrogen peroxide (H2 O2 helps in complete formation of GNPs). Upon HRP inhibition, the enzymatic formation of GNPs was observed to decrease with increasing concentrations of phenylhydrazine (HRP inhibitor) using a simple UV-visible spectrophotometer. The current method provides an in situ enzymatic assay based on the biocatalyzed rate of GNP formation for the rapid, reproducible, and cost-effective detection of phenylhydrazine with a detection limit of 4.02 μM (range: 25–200 μM). The proposed technique was also successfully tested in real samples like drinking, tap, and garden water, emphasizing its usefulness for the direct on-site monitoring of phenylhydrazine, and the concept can be extended for the detection of other inhibitors of peroxidase also.